Purificação e caracterização parcial de inibidores de serino protease e sua influencia sobre a viabilidade espermática equina nos processos de resfriamento e congelamento - Andre Belico de Vasconcelos (2008)
Semen cryopreservation offers great advantages to equine reproduction programs by bringing genetic gain to them. Cryopreservation, however, reduces the quality of sperms due mainly to changes in sperm membranes similar to those which occur during sperm capacitation. Using seminal plasma proteins in the cryopreservation process may minimize deleterious effects on spermatozoa resulting from the action of cryopreservation process, making it valuable to improve the quality of equine spermatozoa both frozen and post-freezing. Thus, the purposes of this work were: identifying preventive procedures of deleterious effects from cryopreservation, investigating the effectiveness of molecular exclusion chromatography in the study of seminal plasma proteins in mammals, isolating and identifying the presence of serine protease inhibitors in equine seminal plasma, exploring comparatively natural and synthetic serine protease inhibitors as for their inhibiting activity in serine protease (bovine trypsin) enzymatic mechanism, introducing natural and synthetic inhibitors of serine protease in a diluting medium to freeze and thaw equine semen, assessing equine spermatozoa morphometric qualities with flow cytometry and comparing the effectiveness of trypan blue and propidium iodide when assessing equine spermatozoa physical integrity with flow cytometry. Three distinct experiments have been performed. The first of these experiments tested the technical application of molecular exclusion chromatography to identify seminal plasma proteins from three different animal species: equine, canine and caprine. According to evidence, molecular exclusion chromatography has been found to be an effective procedure to identify seminal plasma proteins. The second experiment has isolated, identified and evaluated serine protease inhibitor which is present in equine seminal plasma and its inhibiting potential. It has also explored comparatively natural and synthetic serine protease inhibitors as for their inhibiting activity, assessed the correlation between total protein concentration and serine protease inhibitor concentration of seminal plasma with sexual maturity in stallions. Active proteins have been identified to have a molecular mass of 6.3-7.0 kDa using mass spectrometry. Older stallions have shown a reduced total protein concentration of seminal plasma, but have maintained the concentration of serine protease inhibitors with a significant difference between means. Different serine protease inhibitor isoforms have been found in the semen of all stallions. The third experiment has verified the effect of adding serine protease inhibitors to the freezing and thaw medium of equine semen. There was no significant difference between control and treated groups as for the percentage of spermatozoa with progressive motility, functional plasma membrane, plasma membrane integrity, and intact acrosome and DNA fragmentation. No significant difference has been observed between control and treated groups, after inducing acrosome reaction with ionophore calcium A23187, suggesting that serine protease inhibitors do not block acrosome capacitation and reaction. It enabled comparing the effectiveness of two cromophores, Trypan blue and propidium iodide when assessing equine spermatozoa physical integrity by means of flow cytometry. The use of a staining with a lower value than Trypan blue has become very valuable in studies assessing equine spermatozoa, producing a cost reduction in the flow cytometry technique. The chromatography technique of molecular exclusion has presented important points to purify mammals seminal plasma proteins; making it possible to isolate and identify the presence of serine protease inhibitors in equine seminal plasma, in addition to noting that they present isoforms. The potential to naturally inhibit serine proteases is similar to that of synthetic inhibitors. Nevertheless, mo significant difference has been observed between control and experimental groups as for the action of inhibitors on improving the quality of cryopreserved equine spermatozoa. Further studies on isoform generation, peptide interactive mechanisms with sperm cells, determining N-terminal and adding larger doses of serine protease inhibitor in media containing different cryoprotectants are recommended